The Potentiality of Human Umbilical Cord Isolated Mesenchymal Stem/Stromal Cells for Cardiomyocyte Generation - Abou-ElNaga, Amoura (Stem Cells Cloning, 2020)
BACKGROUND: The new therapeutic strategy of managing cardiac diseases is based on cell therapy; it highly suggests the use of multipotent mesenchymal stem/stromal cells (MSCs). MSCs widely used in researches are known to be isolated from bone marrow. However, this research seeks to use a human umbilical cord (HUC) as an alternative source of MSCs. Since HUC Wharton’s jelly (WJ)-isolated MSCs originate as fetal tissue they are highly preferable for their potential advantages over other adult tissues. METHODS: The researchers used enzymatic digestion to establish a primary HUC-WJ-isolated MSC line. Then, flow cytometry was used to characterize MSCs and hematopoietic stem cells (HSCs) markers’ expression. In addition, the cardiac differentiation capacity of HUC-WJ-isolated MSCs in vitro was investigated by two protocols. Protocol-1 necessitates the dependence on merely 5-azacytidine (5-Aza), whereas in protocol-2, 5-Aza was supported by basic fibroblast growth factor (BFGF). The comparative study between the two protocols was applied by inspecting the ultrastructure of differentiated cells, measuring RT-PCR mRNA cardiac markers and the quantitative detection of cardiac proteins. RESULTS: HUC-WJ isolated MSCs were expressed by CD90(+ve), CD105(+ve), CD106(+ve), CD45(−ve), and CD146(−ve). Remarkable TNNT1, NKX2.5, and Desmin mRNA expression and higher quantitative LDH and cTnI were detected by applying protocol-2. This same protocol-2 induced cardiac morphological features that were revealed by identifying cardiomyocyte-like cells and typical sarcomeres. CONCLUSION: HUC-WJ is proved to be an ethical and effective source of MSCs induced cardiac differentiation, whereas BFGF supports 5-Aza in MSCs-cardiomyocytes differentiation.